1991
DOI: 10.1128/aac.35.4.770
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-entrapped ampicillin in the treatment of experimental murine listeriosis and salmonellosis

Abstract: The tissue distribution of ampicillin entrapped in liposomes was studied in normal noninfected mice and showed that ampicillin concentrated mostly in the liver and spleen. Liposomate ampicillin was significantly more effective than free ampicillin in reducing splenic and hepatic bacterial counts in C57BL/Ka nude mice chronically infected with Listeria monocytogenes EGD. It was also significantly more effective than free ampicillin in reducing mortality in C57BL/6 mice acutely infected with Salmonella typhimuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 9 publications
(13 reference statements)
2
24
0
Order By: Relevance
“…Therefore, the intracellular clearance of Salmonella, mainly in macrophages, requires novel therapeutic strategies. In this regard, liposomal and polymeric nanocarriers have been investigated (4,7). Encapsulating drugs within nanoparticles has the potential to reduce toxicity by providing slow, sustained release and to enhance delivery to the intracellular compartments where the bacteria reside.…”
mentioning
confidence: 99%
“…Therefore, the intracellular clearance of Salmonella, mainly in macrophages, requires novel therapeutic strategies. In this regard, liposomal and polymeric nanocarriers have been investigated (4,7). Encapsulating drugs within nanoparticles has the potential to reduce toxicity by providing slow, sustained release and to enhance delivery to the intracellular compartments where the bacteria reside.…”
mentioning
confidence: 99%
“…Higher intracellular concentrations of antibiotics enhance the antibacterial activity of phagocytic cells against to intracellular infections when compared to the same free drug dose (Emmen and Storm, 1987;Bas et al, 2000). It was reported that LA and ampicillin- Bakker-Woudenberg et al, 1986;Carryn et al, 2003) or experimental salmonellosis (Fattal et al, 1989), listeriosis (Bakker-Woudenberg et al, 1985, 1988Fattal et al, 1991). On the contrary, it was reported that FA had no good bactericidal activity, nor need higher concentrations to the treatment in the intracellular infections caused by non-typeable Haemophilus influenzae (Ahren et al, 2002), non-typhoid Salmonella (Chiu et al, 1999) or experimental salmonellosis (Fattal et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…As seen with nanoparticles, ampicillin-containing liposomes concentrate mainly in the spleen and at a lesser extent in the liver. However, liposomes were shown to be less effective for the treatment of acute S. typhimurium-induced samonellosis than PIHCA nanoparticles (108). A single dose of 0.8 mg liposome-bound ampicillin protected 60% of the treated mice in comparison with 100% protection achieved with nanoparticles (106).…”
Section: Salmonellosismentioning
confidence: 99%
“…Different carriers of ampicillin have been developed in order to increase the antibiotic availability at the intracellular sites where the bacteria reside. Distribution studies in uninfected mice showed that when ampicillin was administered intravenously entrapped into liposomes, it quickly concentrated in the liver and mainly in the spleen (108). Moreover, the efficacy of liposomes and free antibiotic were assessed in Listeria-infected mice.…”
Section: Listeriosismentioning
confidence: 99%